Answer:
Step-by-step explanation:
Answer:
Step-by-step explanation:
If the first floor of the Willis Tower is 21 feet high. and each additional floor is 12 feet high, then the floor heights as we move from one floor to another we keep increasing by 12feets and forms an arithmetic progression as shown;
21, (21+12), (21+12+12), ...
<em>21, 33, 45...</em>
a) To write an equation for the nth floor of the tower, we will have to find the nth term of the sequence using the formula for finding the nth term of an arithmetic sequence.
The nth term of an arithmetic sequence is expressed as ![T_n = a + (n-1)d](https://tex.z-dn.net/?f=T_n%20%3D%20a%20%2B%20%28n-1%29d)
a is the first term = 21
d is the common difference = 33-21 = 45-33 = 12
n is the number of terms
Substituting the given parameters into the formula;
![T_n = 21+(n-1)*12\\T_n = 21+12n-12\\T_n = 21-12+12n\\T_n = 9+12n](https://tex.z-dn.net/?f=T_n%20%3D%2021%2B%28n-1%29%2A12%5C%5CT_n%20%3D%2021%2B12n-12%5C%5CT_n%20%3D%2021-12%2B12n%5C%5CT_n%20%3D%209%2B12n)
<em>Hence the equation for the nth floor of the tower is expressed as </em>
<em></em>
<em></em>
b) To get the height of the 65th floor, we will substitute n = 65 into the formula arrived at in (a)
![T_n = 9+12n\\T_{65} = 9 + 12(65)\\T_{65} = 9+780\\T_{65} = 789 ft](https://tex.z-dn.net/?f=T_n%20%3D%209%2B12n%5C%5CT_%7B65%7D%20%3D%209%20%2B%2012%2865%29%5C%5CT_%7B65%7D%20%3D%209%2B780%5C%5CT_%7B65%7D%20%3D%20789%20ft)
<em>Hence the height of the 65th floor is 789feets.</em>
Answer:
I think it would be fine if they notified you but only if they used me for a good reason.
<em>On the other hand...</em>
no matter if it's on the agreement if it is inappropriate on your part it is illegal and you can complain.
The expression simplifies to 13.
There are no exponents or parentheses, so that can be skipped. Start with multiplication and division from left to right.
25-4×9÷2+12÷4×2
25-36÷2+3×2
Add and subtract from left to right.
25-18+6
7+6
13
Answer:
y = - 3x + 4
Step-by-step explanation:
The equation of a line in slope- intercept form is
y = mx + c ( m is the slope and c the y- intercept )
Calculate m using the slope formula
m = (y₂ - y₁ ) / (x₂ - x₁ )
with (x₁, y₁ ) = (0, 4) and (x₂, y₂ ) = (2, - 2) ← 2 points on the line
m =
=
= - 3
Note the line crosses the y- axis at (0, 4) ⇒ c = 4
y = - 3x + 4 ← equation of line